Optimum Selection of Structure Form and Materials for Highway Tunnel Insulation Layers. Issue 1 (October 2020) - Li, Borong; Han, Changling; Fu, Zhipeng
Abstract: At present, the design of tunnel insulation layer in cold area mostly depends on engineering analogy, and the rationality of the design cannot be guaranteed. Therefore, in this study, on the basis of an ANSYS finite element analysis model, boundary conditions and calculation parameters are determined for the Jiangluling Tunnel in the cold region of Tibet, China. An analysis of the different laying methods of the thermal insulation layer between the permafrost section and the non-permafrost section is conducted, along with a comprehensive evaluation of several commonly used thermal insulation materials. Based on the results, the double layering method is recommended for the thermal insulation layer of the permafrost section. The commencement of the freeze–thaw cycle can be delayed by laying the insulation layer in the non-frozen soil section, and laying outside the wall is usually preferred. When the off-wall laying is not possible, the surface laying method is preferred.